Complementary Feeding Methods: Associations with Feeding and Emotional Responsiveness - Carla Fernandes; Fátima Martins; Ana F. Santos; Marília Fernandes; Manuela Veríssimo (MDPI AG, 2023)
Learning to eat complementary foods is a crucial milestone for infants, having implications across development. The most used method for introducing complementary foods is Traditional Spoon-Feeding (TSF). However, the alternative method Baby-Led Weaning (BLW) is increasingly becoming used as it has been associated with positive outcomes. Research analyzing associations between complementary feeding methods and responsive parenting is practically non-existent. Therefore, the objective of this study was to analyze differences in emotional and feeding responsiveness between caregivers who previously implemented traditional vs. non-traditional feeding approaches. Caregivers (mostly mothers) of 179 children between 3 and 5 years were asked about the complementary feeding method that they had followed previously (70.4% reported using the TSF, 16.8% said they used the BLW and 12.8% used both methods simultaneously). In addition, they reported on their feeding practices using the Comprehensive Feeding Practices Questionnaire and on their responses to children's distress using the Coping with Children's Negative Emotions Scale. The results showed that parents who reported using a non-traditional (BLW or both) complementary feeding method reported less pressure to eat and minimization of reactions to children's negative emotions, compared to parents who used a traditional method (although these reported using more problem-focused reactions). The findings suggest that complementary feeding methods and responsive parenting may be linked, leaving the question of which one sets the stage for the other.